1999
DOI: 10.1111/j.1469-8749.1999.tb00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Apneustic breathing in children with brainstem damage due to hypoxic–ischemic encephalopathy

Abstract: To confirm the presence of apneusis in patients with hypoxic–ischemic encephalopathy and to clarify which factors influence their respiratory patterns, polygraphic studies were performed on two patients. Apneusis was clinically suspected in both patients who had severe brainstem damage. In one subject, inputs of vagal afferents from the gastrointestinal tract and the urinary bladder often resulted in extreme tachypnea instead of apneusis. Lung inflation facilitated expiration during inspiratory arrest. Expirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Interestingly, in humans, both the 5-HT 1A R agonist, buspirone, and the 5-HT 4(a) R agonist, mosapride, were found to be ineffective in compensating opioid-evoked respiratory depression (Lö tsch et al 2005;Oertel et al 2007). The ineffectiveness of buspirone in humans is surprising and disappointing: first, in humans, buspirone has been used to reverse major respiratory arrhythmias including apneusis (Wilken et al 1997;Saito et al 1999;El-Khatib et al 2003;Richter et al 2003;O'Sullivan et al 2008). Second, in the rat, both recent evidence (Sahibzada et al 2000;Guenther et al 2009;Manzke et al 2009) and data from the present study show a potent recovery from opioid-evoked respiratory and, in part, cardiovascular suppression with the administration of 8-OH-DPAT.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Interestingly, in humans, both the 5-HT 1A R agonist, buspirone, and the 5-HT 4(a) R agonist, mosapride, were found to be ineffective in compensating opioid-evoked respiratory depression (Lö tsch et al 2005;Oertel et al 2007). The ineffectiveness of buspirone in humans is surprising and disappointing: first, in humans, buspirone has been used to reverse major respiratory arrhythmias including apneusis (Wilken et al 1997;Saito et al 1999;El-Khatib et al 2003;Richter et al 2003;O'Sullivan et al 2008). Second, in the rat, both recent evidence (Sahibzada et al 2000;Guenther et al 2009;Manzke et al 2009) and data from the present study show a potent recovery from opioid-evoked respiratory and, in part, cardiovascular suppression with the administration of 8-OH-DPAT.…”
Section: Discussionmentioning
confidence: 53%
“…Results from investigations in the rat demonstrate identical respiratory responses to 8-OH-DPAT and buspirone (Sahibzada et al 2000;Manzke et al 2009). Further, buspirone has been used effectively in the treatment of apneustic disturbances in man (Wilken et al 1997;Saito et al 1999;El-Khatib et al 2003;Richter et al 2003;O'Sullivan et al 2008). We suggest that clinically the 5-HT 1A R agonist such as buspirone could serve as a pharmacological intervention to avoid and/or recover m-OR-evoked cardiorespiratory disturbances.…”
Section: (C) Summary and Clinical Implicationsmentioning
confidence: 83%
“…Reflex responses to face stimulation, which follow the trigeminal pathway, are integrated in the brainstem, and are good clinical markers of lesions or dysfunctions of the brainstem centers involved in respiration, as well as of other associated autonomic responses, such as cardiovascular responses. Saito et al 38 suggested that the association of diving reflex with the etiopathogenesis of sudden infant death syndrome, particularly in the presence of brain damage, such as severe bilateral hypoplasia of the basal nuclei and gliosis of the other cardiorespiratory medullar nuclei.…”
Section: Discussionmentioning
confidence: 99%